Pemberian Vaksin Ichthyophthirius multifiliis untuk Mencegah Ichthyophthiriasis pada Ikan Mas (APPLICATION OF ICHTHYOPHTHIRIUS MULTIFILIIS VACCINE FOR PREVENTION OF ICHTHYOPHTHIRIASIS IN COMMON CARP) - Syawal, Henni; Kusumorini, Nastiti; Manalu, Wasmen; Affandi, Ridwan (Jurnal Veteriner; Vol 17 No 1 (2016), 2016)
This study was conductedto assess the physiological responses of commoncarp due to administrationof ich vaccines and kept at different water temperatures. Completely Randomized Factorial Designwasusedin this study. The number and the size of the experimental fish was720 and 5-7 cm, respectively. Fish wasvaccinated by immersing the fish in water that contained 3 mLL-1 of ich vaccines for 15 minutes. Then, fishwas kept for 21 days at various temperatures: at 18ºC which was room temperature without heater andfish had not been vaccinated and at 20, 24, and 28ºC where fish was given the vaccines and the aquariumis facilitated with electric heater. Atday15post immunization, challenge test with 5.000 cells of life therontfish-1was performed.Immobilization test, differential leukocyte, prevalence rates, and survival rates weremeasured. The measurements of these parameters were performed four times:before the treatment (day0), day7, day14, and day21, respectively. The results showed that the vaccine could reduce the stress inthefish that were kept at 20, 24, and 28ºC, and the prevalence of ichthyophthiriasis. In addition the vaccineincrease the fish survival rates after challenge test. The highest survival rate (100%) was found in fish thatwerekept in 28ºC.
Keywords: CyprinuscarpioL; Ichthyophthiriusmultifiliis; temperature; vaccine